ROZWÓD NERONA I OKTAWII, CZYLI NOWA LUKRECJA - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
Octavia’s and Nero’s Divorce i.e. New Lucretia Summary Nero had three wives: Octavia, Poppaea and Statilia Messalina. The story of his private life is extremely interesting from the legal point of view. The emperor declared that he wanted to rule according to Augustus’ regulations. However, he soon started to break the most basic rules of the Augustan marital laws. He attempted to marry a freedwoman called Akte, but changed his mind afterwards. In 62 AD he decided to divorce his first wife Octavia on the grounds of sterility in order to marry his lover Poppaea Sabina. Octavia was twice accused of adultery: the first time with a slave and then with Anicetus, the very man who killed Nero’s mother Agrippina. The first charge was probably brought iure extranei and a quaestio was held. The second time it was Nero who accused Octavia iure mariti before a consilium. She was also suspected of plotting against her husband in order to take over the imperial navy commanded by Anicetus. Both these charges led to Octavia’s exile to Pandateria and finally to her death.